Event‐related potentials of social comparisons in depression and social anxiety - Paz, Valentina; Nicolaisen‐Sobesky, Eliana; Fernández‐Theoduloz, Gabriela; Pérez, Alfonso; Cervantes Constantino, Francisco; Martínez‐Montes, Eduardo; Kessel, Dominique; Cabana, Álvaro; Gradin, Victoria B. (Psychophysiology, 2024)
Social comparison is central in human life and can be especially challenging in depression and social anxiety. We assessed event‐related potentials and emotions using a social comparison task in which participants received feedback on both their own and a co‐player's performance, in participants with depression and/or social anxiety (n = 63) and healthy controls (n = 72). Participants reported more negative emotions for downward (being better than the co‐player [participant correct, co‐player wrong]) and upward (being worse than the co‐player [participant wrong, co‐player correct]) comparisons versus even outcomes, with these effects being stronger in depression and social anxiety. At the Medial Frontal Negativity, both controls and depressed participants showed a more negative amplitude for upward comparison versus both the participant and co‐player performing wrong. Socially anxious subjects showed the opposite effect, possibly due to greater expectations about being worse than others. The P300 decreased for downward and upward comparisons compared to even outcomes, which may relate to the higher levels of conflict of social inequality. Depressed and socially anxious subjects showed a blunted P300 increase over time in response to the task outcomes, suggesting deficits in allocating resources for the attention of incoming social information. The LPP showed increased amplitude for downward and upward comparison versus the even outcomes and no group effect. Emotional findings suggest that social comparisons are more difficult for depressed and socially anxious individuals. Event‐related potentials findings may shed light on the neural substrates of these difficulties. This is the first study investigating neural responses to social comparison in participants with symptoms of depression and social anxiety, and healthy controls. Results showed heightened negative emotions and distinct event‐related potentials in participants with these disorders compared to controls. Findings suggest difficulties in dealing with the cognitive and emotional demands of social comparison in depression and social anxiety.